Kualitas Climate-Related Disclosures atas Rekomendasi TCFD pada Perusahaan Multinasional Periode 2020-2022 - Limtaroli, Cindy; Meiden, Carmel (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
The phenomenon of climate change has attracted world attention, as related cases, such as greenwashing, have been carried out by various entities in the world. TCFD is present to provide guidelines for disclosing risks and opportunities, providing stakeholders with information regarding strategy, the carbon emissions in the sector and the company's financial system. The purpose of this research is to analyze the quality of company’s climate-related disclosures and provide comparison between sectors and countries. The objects of research are banking and mining sector companies from China, the United States, and Canada which issue climate-related disclosures for the 2020-2022 period. Data is analyzed using content analysis method and quantitative and qualitative scoring. The research show that quality of “average-high” results, with governance category ranked first quantitatively while metrics and targets category qualitatively. Comparison between countries in order from highest to lowest value is the United States, Canada and finally China. The banking sector shows higher quality of climate-related disclosures than the mining sector.